Sailing through maritime tourism : an analysis of the sailing charter sector in Portugal - Vilarinho, Manuel (2024)
Portuguese maritime tourism industry is witnessing increasing demand for distinctive nautical experiences and, this thesis will explore the dynamics of the sailing charter sector, with the intension to understand market trends, customer preferences and level of competition within the industry. The study begins with a comprehensive demographic analysis of potential customers, providing information on factors such as, age distribution, marital status, occupation and income levels. However, it also draws attention to the possible bias associated with the survey distribution method, underscoring the need for caution when interpreting the results obtained. Furthermore, a sectorial analysis, supported by Informa D&B, provides insightful information about the financial landscape and business environment of Portuguese maritime tourism industry. With the use of this of this analysis, it is possible to study, market’s dimension, financial performance and potential opportunities and threats for new entrants in this sector. In the final chapters, this thesis provides a diagnosis of the industry, highlighting key players, market trends and competitive dynamics. It emphasizes the importance of financial stability and reinforces customer’s willingness to pay premium prices for longer-duration services. In conclusion, this thesis offers a thorough analysis of Portugal’s sailing boat charter market, offering valuable insightful information for industry stakeholders and entrepreneurs. It underscores the necessity for more research and planning in order to take advantage of new opportunities and overcome obstacles in this dynamic and evolving sector.